Pattern of care of blood donors with early‐uncomplicated hereditary haemochromatosis in a Swiss blood donation centre. Issue 2 (2nd September 2013) - Stefashyna, O.; Stern, M.; Infanti, L.; Holbro, A.; Tichelli, A.; Buser, A.; O'Meara, A.
<x xml:space="preserve">Abstract</x> Background and Objectives We describe the recognition and pattern of care of voluntary blood donors with early‐uncomplicated genetic haemochromatosis in our blood donation centre. Materials and Methods Asymptomatic volunteers with suspicion of hereditary haemochromatosis (HH) due to an elevated ferritin level on routine screening were referred for further investigation. Alternatively, we accepted subjects with prediagnosed HH on referral. In the case of early‐uncomplicated genetic haemochromatosis, either standard whole blood donation (WBD) or double‐erythrocytapheresis (DEC) was offered. Results A median of six procedures was needed to achieve a ferritin value below 100 ng/ml in the WBD group and of four in the DEC group (P = 0·5). The rate of donation side‐effects was higher in the DEC group, while the costs it generated were equivalent to WBD. Conclusion Compared with WBD, DEC had no beneficial effect on treatment number, length of treatment, side‐effects or treatment budget in early‐uncomplicated HH. Integrating donors with uncomplicated genetic haemochromatosis to blood donation programmes can supplement blood stores and provide the donors with a cost‐effective and altruistic purpose of treatment.